Assessing the impact of foreign direct investment on regional growth - An analysis of the Spanish case - Oscar Bajo-Rubio; Carmen Diaz-Roldan (European Regional Science Association (ERSA), 2005)
The massive increase in foreign direct investment inflows following the Spanish integration with the now European Union in 1986, has been one of the most important features shaping the behaviour of the Spanish economy in the last twenty years. In this paper we will try to provide an assessment of its impact on regional economic growth, using data for the 17 Spanish regions, from 1986 on. To that end, we will estimate an aggregate production function where the foreign-owned capital stock is included as an additional factor.
Keywords: 330